Dynamic Behavior of Double Steel Sheet Pile Cofferdam under Different Wave Actions. Issue 7 (October 2021) - Zhu, Y; Li, X J; Shi, Z M; Peng, M; Xuan, L J; Gao, J Y; Cai, S
Abstract: Double-row steel sheet piles, which have good dynamic stability, strong deformability, high seepage resistance, and strong engineering adaptability, have been widely used as coastal defense structures. The paper investigates the dynamic behavior of the double-row steel sheet pile cofferdam under the actions of breaking-wave and standing-wave through large-scale flume model test. High-frequency optical fiber technology was applied to obtain the stress data on the steel sheet pile. It was found that the standing wave produced a cycle action of crest pressure and trough suction to the DSSP cofferdam, forming a scour pit at the toe of the seaside steel sheet pile. The breaking wave did not produce obvious reflection and suction against the DSSP but incurred huge crushing energy and large deformation on the DSSP cofferdam. The bending moment on the steel sheet pile under near the breaking wave is about 2 to 3 times that under the standing wave. The deformation of the steel sheet pile may cause leakage of the joint and soil erosion of the in-filled sands, even resulting in failure of the DSSP cofferdam.